KUALITAS PELAYANAN PUBLIK BERBASIS DIGITAL TERHADAP TINGKAT KEPUASAN MASYARAKAT DI DESA BULO - Saputri, Annisa; Lukman; Uceng, Andi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The aim of this research is to determine the quality of digital-based public services and the level of community satisfaction in Bulo Bulo village as well as the influence of digital-based service quality on the level of community satisfaction.The population in this study was 182 people and the sample was 64 people. The sampling technique is nonprobability sampling. This type of research is Quantitative Associative. The data collection techniques used in this research were observation, questionnaires and literature study. The data analysis techniques used are measurement scale instruments, reliability testing and simple linear regression analysis using SPSS 16.0 and a Likert Scale. The results of this research from the results of the questionnaire obtained a recapitulation of the service quality variable of 67% in the